GLAUCOMA SECONDARY TO NONSPECIFIC ORBITAL INFLAMMATION: A DIAGNOSIS NOT TO OVERLOOK: Poster Presentation - Case Report - Resident - Prakoeswa, Camilla Amanda; Komaratih, Evelyn; Fatmariyanti, Susy (Majalah Oftalmologi Indonesia, 2023)
Introduction : Nonspecific Orbital Inflammation (NSOI) is an inflammatory condition of unknown etiology manifesting as pain, ocular motility disturbances, eyelid edema, chemosis, and increased intraocular pressure (IOP). We illustrate a case of glaucoma secondary to NSOI and the importance of understanding the cause-effect relationship between the two conditions. Case Illustration : An eighteen-year-old girl presented with severe pain, ptosis, chemosis, ophthalmoplegia, and increased IOP (38 mmHg) despite a leaking trabeculectomy bleb, on the left eye. She was referredwith the diagnosis of primary angle-closure glaucoma (PACG) and a history of twice trabeculectomy surgeries done elsewhere two months before she came to our hospital. She could not move her lefteye nasally five months before the first surgery and felt joint pains for a year. After thorough diagnostics, she was assessed with left eye NSOI and secondary glaucoma with spondyloarthropathy. Oral prednisone 30 mg/day was given to manage the inflammation and the resultant glaucoma. One week follow-up showed an improved condition with decreased IOP (16 mmHg) despite the same anti-glaucoma therapy regimen. Discussion : NSOI can mimic various diseases, making diagnosis challenging. The raised IOP in NSOI is often caused by extraocular muscles and orbital tissue swelling, which compresses the superior and inferior ophthalmic veins, resulting in choroidal circulation problems. The IOP was quickly reduced once the inflammation was managed. This is a case of secondary glaucoma caused by an overlooked NSOI, aggravated by the immunological process in the orbit after trabeculectomy surgeries. Conclusion : Secondary glaucoma should be considered as a differential diagnosis of PACG in patients with NSOI.